THE IMPLEMENTATION OF PROFESSIONAL COMPETENCE OF ENGLISH TEACHERS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE (A CASE OF TEACHERS IN SMU NEGERI 1 SOE)) - yabes olbata; Ferdinandus Mone (Universitas Wiralodra, 2021)
The teacher is considered as the most crucial factor in implementing all educational reforms at the very basic level. In order to get the good result in education, it needs competent teachers. This study aims at finding out the way teachers implement their professional competence in the form of knowledge mastery, creativity and use of media in teaching English as a foreign language. This study used qualitative descriptive design. The instruments used were observation and interview. The data of this study was collected through doing observation and interview. The data of this study were analyzed by using Miles and Huberman’s model of analysis (Flow Model). The result of the study showed that the way teachers implemented their professional competence in the form of knowledge mastery, creativity and use of media were done well. Based on the result of the study, it can be concluded that the teachers implemented their professional competence well in teaching and learning process.